Pengaruh Jumlah Tenaga Kerja Dan Investasi Terhadap Pertumbuhan Ekonomi Dengan Zakat Sebagai Variabel Moderasi - Mazroatul Hasanah; Mohammad Sholeh; Devy Arisandi (Journal Of Islamic Economics And Finance, 2025)
This study aims to analyze the influence of the number of workers and investment on economic growth in Indonesia with zakat as a moderating variable during the 2020–2023 period. Using a quantitative approach, this research employs panel data obtained from BPS, BKPM, and BAZNAS, consisting of 128 observations across 32 provinces. The data were analyzed using Moderated Regression Analysis (MRA) with Eviews-10, preceded by descriptive analysis, stationarity tests, classical assumption tests, and model selection through Chow, Hausman, and LM tests. The results show that both the number of workers and investment have a significant positive effect on economic growth. Zakat is found to significantly moderate the relationship between the number of workers and economic growth, indicating that zakat distribution can enhance the contribution of labor to economic performance. However, zakat does not moderate the effect of investment on economic growth, suggesting that zakat funds are still dominantly allocated for consumptive rather than productive activities. In conclusion, strengthening zakat management, enhancing labor competence, and improving investment effectiveness are essential to support sustainable economic growth in Indonesia.